Ireland: The weak European supervision of prison policies and its explanations - Rogan, Mary (My University, 2022)
Ireland has a long history as a member state of the Council of Europe and its supervisory mechanisms. Given the absence of the European Court of Human Rights case law regarding Ireland, this chapter will focus on the impact of the European Convention on Human Rights (ECHR) on domestic case law in relation to prisons alongside the activities of the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment (CPT), as well as the influence of European standards on domestic law and policy. We also provide analysis of how European human rights protections are viewed by people in prison. We posit that the weak judicial European supervision of prison practices in Ireland derives in part from Irish legal culture's reluctance to use the Convention, as well as a general lack of prison litigation. We argue that Council of Europe's framework for protecting rights in prisons as a whole must be considered when assessing the impact of European supervision on Ireland, especially in the absence of direct supervision by the Strasbourg court, and that non-judicial supervision has had some effect on domestic practice.
The Evolving Protection of Prisoners' Rights in Europe
Keywords: Inclusive Society